Pelatihan Pemanfaatan Aplikasi Quizizz Bagi Guru SDN 9 Nagrikaler untuk Meningkatkan Kemampuan Literasi Numerasi Matematis Siswa - Wida Utari; Enjelita Robintang Tambunan; Intan Chintyawati Arrasyid; Mezy Fauziyah; Rifa Hasna Nisrina; Yesika Damanik; Anwar Mulyana; Hafiziani Eka Putri; Nadia Tiara Antik Sari (Universitas Pendidikan Indonesia Kampus Purwakarta, 2021)
The Covid-19 pandemic has been impacting practically all aspects of life, including aspects of education. During this pandemic, all activities of learning are going online. It takes advantage of information technology as a medium. This training was held to improve the SDN 9 Nagrikaler Purwakartas' teacher's ability to use the Quizizz application for elementary school teachers. By this application, It can rectify the elementary students' mathematical numeracy skills. This training was held in 3 stages: (1) pretraining, (2) implementation of training (3) post-training. The first stage of preparation before training was setting up the preparation of events, materials, questionnaires, etc. Then, the training stage was filled with pretraining questionnaire distribution, explanation, and direct practice of using the Quizizz application by creating questions related to mathematical numeration literacy. The final stage was filled with message impressions, post-training questionnaires, and interviews with a headmaster and teacher deputations. The result of this training is that 95% of teachers are interested in using the Quizizz application. The conclusion from this training was that Quizizz training needs to be appertained because of this pandemic. A variety of learning is needed for boosting the motivation of learning. This Quizizz training went decently. It can be seen from the teacher's enthusiasm in following the stages of making questions in the Quizizz application.